Digital Dental X-Ray Image Segmentation and Feature Extraction - Abdolvahab Ehsani Rad; Mohd Shafry Mohd Rahim; Alireza Norouzi (Institute of Advanced Engineering and Science, 2013)
The process of analysis of such images is important in order to improve quantify medical imaging systems. It is significant to analysis the dental x-ray images we need features of image. In this paper we present a method for segmentation and feature extraction of dental x-ray images. The proposed method has been implemented by using level-set method for segmentation after image enhancement and illustrate contour for teeth to complete the segmentation step. Furthermore, we extracted multiple features of dental x-ray images using texture statistics techniques by gray-level co-occurrence matrix. Extracted data can perform to obtain the teeth measurements for automatic dental systems such human identification or dental diagnosis systems. Preparatory experiments show the significance of the proposed method to extract teeth from an x-ray image. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2655